Permeability test on reinforced clayey sand - Chegenizadeh, Amin; Nikraz, Hamid (World Academy of Science, Engineering and Technology, 2011)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fiber inclusion on permeability of composite soil (i.e. sand composite). A series of laboratory permeability tests carried out to evaluate fiber effect on hydraulic conductivity behavior of composite sand. Clayey sand was selected as soil part of the composite and natural fiber was used as reinforcement. The fiber parameters differed from one test to another, as fiber length were changed from 10 mm to 25 mm and fiber content were varied from 0.1% and 0.3%. For each test, permeability coefficients derived and the results were compared. The results proved that inclusion of fiber affected hydraulic conductivity of sand composite so that increasing in fiber content and length caused increasing in permeability coefficients.